Measured effect of emotional intelligence education in the remediation of aggressive behaviours among members of the NURTW in Ibadan metropolis (2007)
The study investigated the effects of Emotional Intelligence education in the remediation of aggressive behaviours among the members of the National Union of Road Transport Workers (NURTW) in Ibadan metropolis. Eighty-nine (89) member of the NURTW who were randomly selected from Gate, Molete and Iwo Road motor parks in Ibadan whose ages ranged between 17-65 years with a mean of 41 were randomly assigned to the intervention condition and the control group. The training lasted for six weeks of 12 sessions. A pre-test post-test control group design using a 2x3 factorial matrix was utilized. The participants responded to an Aggression Questionnaire by Buss and Perry (1992) at the pre and post intervention sessions. The result indicated that the intervention group had their aggressive behaviour tendencies greatly reduced compared with the control group. [(1,83) = 121.83 P<.001], an indication of a significant difference between the experimental and the control group. On the basis of the findings, it was suggested that members of the NURTW should be trained in emotional intelligence skills which could successfully reduce, remediate and alleviate their aggressive behaviours. This would lead to an enhanced relationship between the members of NURTW and the passengers, an enhanced intra and interpersonal relationship among members of the union, reduced rate of recklessness and avoidance of bloody clashes among rival groups of the union